COMPARISON OF RIMAN, LEBEG, LEBEG-STILTES, RIMAN-STILTES INTEGRALS - B. Mamadaliyev; M. Rahmanov (Galaxy International Interdisciplinary Research Journal, 2023)
This in the article Compare Riemann, Lebesgue, Lebesgue-Stiltes, Riemann-Stiltes integrals basics given .